Caveats and Pitfalls of SOX1 Autoantibody Testing With a Commercial Line Blot Assay in Paraneoplastic Neurological Investigations - Ruiz-García, Raquel; Martínez-Hernández, Eugenia; García-Ormaechea, Milagros; Español-Rego, Marta; Sabater, Lidia; Querol, Luis; Illa, Isabel; Dalmau, Josep; Graus, Francesc (Frontiers in Immunology, 2019)
SOX1 autoantibodies are considered markers of small cell lung cancer (SCLC) and paraneoplastic neurological syndromes (PNS) and are usually determined by commercial line blot in many clinical services. Recent studies suggested that SOX1 autoantibodies also occur in patients with neuropathies unrelated to SCLC, questioning the value of SOX1 autoantibodies as paraneoplastic biomarkers. Here, we compared the specificity and sensitivity of a commercial line blot (Euroimmun, Lübeck, Germany) with those of an in house cell-based assay (CBA) with HEK293 cells transfected with SOX1. Overall, 210 patients were included in the study, 139 patients with polyneuropathies without SCLC and 71 with disorders associated with SOX1 autoantibodies detected with the in-house CBA. Forty one of these 71 cases had been referred to our laboratory for onconeuronal antibody assessment and 30/71 were patients with known PNS and SCLC. None of the patients with polyneuropathies had SOX1 autoantibodies by either line blot or CBA (specificity of the immunoblot: 100%; 95%C.I.: 97.8-100). Among the 71 patients with CBA SOX1 autoantibodies, only 53 were positive by line blot (sensitivity: 74.6%; 95%C.I.: 62.9-84.2). Lung cancer was detected in 37/41 (90%; 34 with SCLC) patients referred for onconeuronal antibody assessment and 34 of them also had a PNS. Our study confirms the association of SOX1 autoantibodies with SCLC and PNS. The line blot test misses 25% of the cases; therefore, to minimize the frequency of false negative results we recommend the use of a confirmatory test, such as CBA, in patients suspected to have a SCLC-related PNS.